Evaluation of the performance of a Ho: Sc2SiO5 laser pumped by a Tm:YAP laser. (13th April 2016) - Yang, Xiao-tao; Xie, Wen-qiang; Li, Wen-hui; Li, Xue-min
Abstract: A continuous-wave 0.5 % Ho 3+ -doped Ho:Sc2 SiO5 (Ho:SSO) laser output at 2112 nm pumped by a Tm:YAP laser is reported. The Ho:SSO bulk crystal was grown by the Czochralski technique. A maximum laser power of 3.72 W was obtained with a slope efficiency of 32.9%, when the transmittance of output mirror was 30%. In this experiment, two output mirrors with different transmittance were also researched. The output spectra of Ho:SSO laser with different output mirrors are also given. The M 2 factor is found to be 1.29. In addition, the absorption and emission spectra are given in this paper.